Optimalisasi Jumlah Tenaga Kerja Langsung Pada Perusahaan Produsen Air Minum Dalam Kemasan - solihah, Nabilatus; Aang Kunaifi (Program Studi Ekonomi Syariah, STAI AN-NAJAH INDONESIA MANDIRI, 2024)
Production efficiency is the main factor in controlling the cost of production. This control is carried out to achieve the ideal cost of production and have competitiveness. One of the substantive elements of the Cost of Production (HPP) is direct labor costs. This study was conducted to determine the optimal number of direct workers in a bottled drinking water manufacturing company. Optimization of determining the number of direct workers in this study was carried out by analyzing the company's historical data, including the expected production volume, volume and workload of each employee in a certain period, effective working days and hours of each employee, historical data on employee absence rates, and the frequency of employee entry and exit. Data obtained from the company's personnel and finance departments were collected to be classified and validated with confirmation from the personnel manager and finance manager. After being confirmed and validated, an analysis was carried out using the Work Force Analysis (WFA) approach to determine the number of workers in each sub-section in direct labor (production sector). Based on the results of the study, it was found that the company experienced excess labor in certain sections and labor shortages in other sections. Based on the analysis, the company should determine the accurate number of direct laborers to obtain the expected production with efficient costs. The implications of the results of this study indicate the importance of calculating and determining the accurate number of direct labor to achieve the company's goals. Keywords: Optimizing, labour, WFA, efficiency.